Internal parasites of dogs - ΓΕΩΡΓΟΥΛΑΚΗΣ ΓΙΑΝΝΗΣ EM. (Journal of the Hellenic Veterinary Medical Society, 2019)
More than 50 Kinds of worms have been reported in dogs. AD dogs, including new born puppies and old dogs, have parasites and are affected by them. Many of the dog parasites can affect human beings. Ascaride, hookworms, whipworms (which are three kinds of roundworms) and tapeworms are the most frequently encountered and best known